An Unusual Case of Hemophagocytic Lymphohistiocytosis Presentation in Acute Human Immunodeficiency Virus. (June 2021) - Jariwal, Roopam; Jaber, Fouad S.; Ipalawatte, Harendra; Petersen, Greti
Hemophagocytic lymphohistiocytosis (HLH) in acute human immunodeficiency virus (HIV) patients has been scarcely reported in the English literature. To the best of our knowledge, only 12 cases have been described. We present a case of a 27-year-old male with no past medical history who was admitted with a new-onset headache, fever, night sweats, and chills. Further laboratory tests revealed transaminitis, leukopenia, thrombocytopenia, positive HIV antigen/antibody test, and markedly elevated ferritin levels, which promoted our suspicion of HLH. This case demonstrates HLH as an unusual presentation of HIV during its seroconversion stage. This report adds a rare disease process to the available literature, and we emphasize that markedly elevated ferritin levels in acute HIV patients should raise suspicion toward a diagnosis of HLH.